Dementia in an Acute Hospital Setting: Health Service Research to Profile Patient Characteristics and Predictors of Adverse Clinical Outcomes - Singh, Inderpal (Geriatrics (Basel), 2019)
Introduction: Patients with dementia often have other associated medical co-morbidities resulting in adverse outcomes. The National Audit of Dementia (NAD) in the UK showed a wide variation in the quality and clinical care for acute dementia patients. This study aims to record the clinical profile and benchmark clinical outcomes of acute dementia patients admitted within Aneurin Bevan University Health Board, Wales (UK). Methods: This was a retrospective observational study based on analysis of the existing data for all acute dementia patients. Ethical approval was not required for this service evaluation. Results: In 2016, a total of 1770 dementia patients had 2474 acute admissions. We studied 1167 acute admissions (953 dementia patients) from 1st January 2016–30th June 2016. The mean age was 84.5 ± 7.8 years (females = 63.5%). Mean Charlson comorbidity index and the number of drugs were 6.0 ± 1.5 and 5.1 ± 2.1. 15.4% (147/953) patients were on antipsychotics. Overall mean hospital stay was 19.4 ± 27.2 days. 30-days readmission rate was 17.2% (138/800) with a mean hospital stay of 14.6 ± 17.9 days. 3.4% (32/953) patients were excluded due to a coding error. 70.3% (n = 670/953) were previously living in their own homes and only 26.3% (n = 251/953) were admitted from care homes. 59.5% patients (n = 399/670) were discharged back to their homes and 21.6% (145/670) were discharged to a new care home, which represents an approximately 1.68 times higher rate of new care home occupancy than the patients being originally admitted from a care home. Overall inpatient was 16.0% (153/953). 30-days and one-year mortality were 22.3% (213/953) and 49.2% (469/953) respectively. The observed mortality rates between patients admitted from home or from a care home were highly significant for one-year mortality (p < 0.001). The inpatient falls rate was significantly higher (1.8 times) as compared to overall general medical inpatient falls rate. Conclusion: Acute patients with dementia have a higher risk of adverse outcomes and the impact of hospitalisation. Prompt comprehensive geriatric assessment and quality improvement initiatives are needed to improve clinical outcomes and to enhance the quality of care.